Gender Differences in the Language of Mathematics in Secondary Schools - Makungu Bulayi (International Journal of Trends in Mathematics Education Research, 2020)
This study investigated gender difference in students’ understanding of the language of mathematics at ordinary secondary school level in Tanzania. The participants were 489 students from 8 ordinary secondary schools. An achievement test that comprised of the language of mathematics and algorithmic skill tests was administered. The findings indicated that, there is no significance difference between boys and girls in the understanding of the language of mathematics. The participant students had a fair knowledge of mathematical terms with direct meaning in the common English language usage. It is recommended that, mathematics teachers should put into consideration the teaching of the language of mathematics in mathematics classrooms and equally encourage both boys and girls to understand the language of mathematics.